Frequency of Category 1 and Category 2 Tuberculosis in District Kotli Azad Kashmir (Medical Forum Monthly, 2024)
Objective: To estimate the frequency of Category 1 and 2 Tuberculosis in area of research.Study Design: Cross sectional studyPlace and Duration of Study: This study was a conducted in District Kotli Azad Kashmir from from January 2009 to December 2009.Material and Methods: This study was conducted with a population of 750,000. Data was collected from all the eight national TB centres in the District Kotli. It included every patient registered there with the diagnosis of tuberculosis including pulmonary and extra pulmonary tuberculosis and sputum smear positive and negative patients. They were classified as category 1 and category 2 according to the standard definitions. Results were given in tabulated form.Results: From a total of 752 patients, 579 (76.99%) were pulmonary and 173 (23%) were extra pulmonary. In pulmonary TB cases, 259 (44.78%) were sputum smear positive [235 (90.73%) of them were category 1 and 24 (9.24%) were category 2]. In 320 (55.26%) sputum smear negative patients, 300 (93.75%) were category 1 and 20 (6.25%) were category 2. All of the extra pulmonary TB cases were category 1 (100%). As a whole 708 (94.15%) were category 1 and 44 (5.85%) were category 2.Conclusion: In our study frequency of category 2 patients was found to be relatively low. It indicates that the problem of drug resistant tuberculosis is probably low in the area. It also shows the effectiveness of local TB control programme.